An ethnobotanical survey of edible fungi in Chuxiong City, Yunnan, China - Dongyang Liu; Hong Cheng; Rainer W. Bussmann; Zhiyong Guo; Bo Liu; Chunlin Long (BMC, 2018)
Abstract Background Chuxiong, known as "the City of Fungi," is rich in fungal resources and traditional knowledge related to fungal biodiversity. The local environment is an excellent habitat for a wide variety of edible fungi. In addition, the region is home to many ethnic minorities and especially the Yi ethnic group who has a long history for traditionally using fungi as food or medicine. The aims of this review are to provide up-to-date information on the knowledge about, and traditional management of, fungi in this area and give advice on future utilization and conservation. Methods Field surveys and in-depth semi-structured interviews were used to gather data. Ethnomycological data was collected from 67 informants in the summer of 2015. Results Twenty-two edible fungal species were recorded both as food or non-timber forest products (NTFPs), used to increase income, and the importance of this resource for the Yi ethnic group was evaluated. Conclusion Abundant and diverse wild genetic resources and a large production chain of edible fungi were recorded in Chuxiong. However, because of over-harvesting, the wild edible fungi are facing increasing threats. Suggestions are proposed to allow sustainable use of fungi resources, including (1) promotion of diversification of transportation, (2) development of fungi cultivation to improve quality and supply and reduce harvest pressure, (3) improvement of public awareness for environmental protection and sustainable development, and (4) promotion of eco-tourism and development of fungi catering in rural agro- and slow-food tourism.